Queen of vaudeville : the story of Eva Tanguay - Erdman, Andrew L., 1965- (Cornell University Press, 2012)
Profiles the early twentieth-century vaudeville star who became nationally known for her trend-setting performances and brazen personality, highlighting the historical significance of her sexually-forward performance style.